Chronic brucellosis with hepatic brucelloma and AA amyloidosis in a patient with autosomal dominant polycystic kidney disease - Arpitha Kollabathula; Vikarn Vishwajeet; Kirti Gupta; Suvradeep Mitra; Vibhav Sharma; Pallab Ray; Ashish Bhalla (University of São Paulo, 2020)
We describe an autopsy case of a 45-year-old male diagnosed with autosomal dominant polycystic kidney disease who presented with complaints of altered sensorium. The autopsy revealed multiple tumor-like masses in the liver, which on histological examination depicted multiple large suppurative granulomas with the presence of variable acid-fast coccobacilli (consistent with Brucella spp.). Interestingly, extensive amyloid deposition in multiple organs was noted. To the best of our knowledge, this is the first case of chronic brucellosis causing tumor-like abscesses in the liver accompanied by secondary systemic amyloidosis in a patient with underlying autosomal dominant polycystic kidney disease.